Behaviours of precast concrete wall panel with opening in one way actions under vertical load - Chong, Fung Yun (School of Environmental Engineering, University Malaysia Perlis, 2016)
Reinforced concrete walls panel are tested in one-way action with different configuration of opening. The sizes of the opening were provided in the walls as percentage of total wall area with 5 % and 10 %. To resemble imperfections in construction, the wall panels were subjected to a uniformly distributed axial load with an eccentricity of t/6. Sixteen wall panel with a slenderness ratio or 8 were tested in both software analysis and experiment. In this research, Linear Variable Differential Transformer (LVDT) and data logger is used to collect the experimental data. LUSAS Software with finite element analysis is used to analyse the software data. This research extend the scope of evaluate the behaviour of precast concrete wall panels with opening in one way action under vertical load in term of cracking pattern, load --deflection curve and stress distribution. The results from this study also compare the tolerance between software and experimental. The result shown that the bigger size of opening creates in the reinforced concrete wall reduced the strength of the wall panel whereas the changed in location of opening effect to the failure mechanism of the wall panel. 7 % reduction in axial strength of concrete wall panel with 5 % of opening and followed by 22 % reduction in axial strength of concrete wall panel with 10 % of opening to the surface of wall panel. The changed in location of the opening upward increased the reduction of axial strength to 24 %.